2016
DOI: 10.4268/cjcmm20162108
|View full text |Cite
|
Sign up to set email alerts
|

Potential distribution of Rhodiola crenulata in Tibetan Plateau based on Maxent model

Abstract: Wildlife tending and artificial cultivation is an important way to protect the wild resources of Rhodiola crenulata. It is a study hotspot at present. The distribution information of R. crenulata was collected by query data and field survey, the ecological suitability regionalization was conducted based on maximum entropy model combine with ecological factors, including climate, soil and altitude. To provide the reference for production layout, suitable planting area and the selection of artificial planting ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…At low sample sizes, its accuracy is 1.5 times that of GARP [21,22]. MaxEnt has been widely applied in predicting the suitable and dispersal pathways of invasive species of the future, suitable growing areas for economically important plants, and prioritized conservation areas for endangered species and the response of species spatial distribution to future climate change [23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…At low sample sizes, its accuracy is 1.5 times that of GARP [21,22]. MaxEnt has been widely applied in predicting the suitable and dispersal pathways of invasive species of the future, suitable growing areas for economically important plants, and prioritized conservation areas for endangered species and the response of species spatial distribution to future climate change [23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that RL could improve immunity, resist fatigue, and enhance cell vitality. 10,11 Our previous study showed that the active ingredient of RL could reduce the expression of inflammatory factors and alleviate various organ damage caused by inflammation. However, the mechanisms of RL for the treatment of ALI was still be investigated.…”
Section: Introductionmentioning
confidence: 99%